Analysis on Environmental Impact of the Development of Marine Strategic Emerging Industries and Supervision Countermeasures in China - YANG Zhengxian; WEI Shuyun; WANG Xiaomeng; HAN Jianbo (Haiyang Kaifa yu guanli)
Marine strategic emerging industries have become an important engine for the development of the marine economy and a key development area to achieve the “carbon peaking and carbon neutrality goals” in China. This paper takes offshore wind farms, offshore photovoltaic fields, new marine aquaculture bases, and offshore carbon storage projects as examples to analyze the development trends and environmental impacts of marine strategic emerging industries at home and abroad. Research shows that with the increase of industry types and scale, the environment impact and ecological risks have gradually become apparent. Overall, marine strategic emerging industries in China are in a critical stage of transitioning from new growth points to strategic pillar industries, but environmental impact research and supervisory system are still in the initial stage. In order to promote the green and high-quality development of marine strategic emerging industries in China, it is necessary to strengthen basic research on ecological and environmental impacts, and focus on long-term ecological impacts and disaster risks; develop targeted regulations, standards, and regulatory systems based on industry type, scale, and location; ensure compliance with relevant international conventions, participate or organize actively in the formulation and revision of relevant international policy documents and technical guidelines, and promote international development of marine strategic emerging industries in China.